Are there changes in the nutritional status of children of Oportunidades families in rural Chiapas, Mexico? A cohort prospective study. Issue 1 (December 2016) - García-Parra, Esmeralda; Ochoa-Díaz-López, Héctor; García-Miranda, Rosario; Moreno-Altamirano, Laura; Solís-Hernández, Roberto; Molina-Salazar, Raúl
Abstract Background In Mexico, despite that the fact that several social programs have been implemented, chronic undernutrition is still a public health problem affecting 1.5 million children of <5 years. Chiapas ranks first in underweight and stunting at national level with a stunting prevalence of 31.4 % whereas for its rural population is 44.2 %. The purpose of this paper is to determine if the nutritional status of a cohort of children living in poor rural communities underOportunidades has changed. We were interested in assessing the nutrition evolution of the children who were initially diagnosed as stunted and of those who were diagnosed as normal. Oportunidades is an anti-poverty program of the Mexican government consisting mainly in monetary transfers to the families living in alimentary poverty. Methods A 9-year cohort prospective study was conducted with nutritional evaluations of 222 children. Anthropometric indices were constructed from measurements of weight, height, and age of the children whose nutritional status was classified following WHO standards. Results The results showed that although these children were Oportunidades beneficiaries for 9 years and their families improved their living conditions, children still had a high prevalence of stunting (40.1 %) and 69.6 % had not recovered yet. Children who were initially diagnosed with normal nutritional status and became stunted 2 years later had a higher risk (relative risk (RR) 5.69, 2.95–10.96) of continuing stunted at school age and adolescence. Conclusions Oportunidades has not impacted, as expected, the nutritional status of the study population. These findings pose the question: Why has not the nutritional status of children improved, although the living conditions of their families have significantly improved? This might be the result of an adaptation process achieved through a decrease of growth velocity. It is important to make efforts to watch the growth of the children during their first 3 years of age, to focus on improving the diet of women at fertile age and pay special attention to environmental conditions to break the vicious cycle of malnutrition.